Socioeconomic Impacts of Agglomeration in the Jabodetabek Megalopolis - Nafiah Sholikhatun Jamil; Annis Nurfitriana Nihayah, S.E., M.E. (Jurnal Ekonomi Pembangunan, 2025)
The external benefits of clustering industries and populations, known as agglomeration economies, are central to urban growth, yet rapid development risks generating socioeconomic diseconomies. This investigation empirically assesses the long-term, heterogeneous socioeconomic consequences of agglomeration within the Jabodetabek metropolitan region, Indonesia, over the period 2010 to 2022. Applying the Panel ARDL framework (PMG/MG), the study models the impacts of four key agglomeration proxies: LDEN (population density), LEMP (industrial employment), LFAC (number of factories), and LDHOU (housing demand). Four socioeconomic outcome measures were constructed using Principal Component Analysis: Education, Healthcare, Economic condition, and Water & Sanitation Indices. The findings consistently demonstrate a pronounced and complex trade-off: LFAC and LDHOU are verified as strong, positive drivers for the Health, Economic, and Water & Sanitation Indices. Conversely, high LEMP exerts significant detrimental pressure on these three indices. The Education Index presents a unique dynamic: LDEN is beneficial, while LFAC's and LDHOU's physical expansions negatively affect it, suggesting severe capacity constraints in the education sector. Overall, the results caution that unmanaged agglomeration growth risks widening inter-regional disparities without targeted policy interventions to boost social infrastructure capacity.